A propensity score matching study: The prevalence of mental health problems among pregnant women at first antenatal care increased in Chongqing during the first wave of the COVID-19 pandemic - Jiamei Guo; Xiao Li; Jinglan He; Ming Ai; Yao Gan; Qi Zhang; Anhai Zheng; Wanjun Chen; Lulu Chen; Sisi Liang; Xiaoyu Yu; Li Kuang (Frontiers Media S.A., 2023)
BackgroundThe 2019 coronavirus disease (COVID-19) pandemic increased the risks of mental health challenges, especially anxiety and depression. However, the impact of COVID-19 on mental health during pregnancy has not been fully established. Therefore, we investigated the impact of the COVID-19 pandemic on maternal mental health.MethodsTwo cohorts of pregnant women at their first antenatal care in the First Affiliated Hospital of Chongqing Medical University were enrolled in this study. One cohort was enrolled before the COVID-19 outbreak, from 1 June to 31 December 2019 (n = 5,728, pre-COVID-19 group), while the other was enrolled during the COVID-19 pandemic, from 24 January to 23 March 2020 (n = 739, COVID-19 pandemic group). Symptoms of depression, anxiety, and somatization disorders were assessed by the Patient Health Questionnaire-9 (PHQ-9), Generalized Anxiety Disorder-7 (GAD-7), and Patient Health Questionnaire-15 (PHQ-15), with a cutoff point of 10 for moderate-to-severe depression, anxiety, and somatoform symptoms. The propensity score matching method (1:1) was used to balance differences in demographic characteristics between groups. A chi-square analysis was performed to compare differences in demographic characteristics between the groups.ResultsPrevalence of moderate-to-severe depression, anxiety, and somatoform symptoms among pregnant women at their first antenatal care visit during the COVID-19 pandemic (9.5, 2.2, and 20.8%, respectively) was significantly lower than those before the pandemic (16.3, 4.4, and 25.7%, respectively) (p < 0.05). Compared with the same period before the pandemic, during the pandemic, the number of women newly registered for antenatal care decreased by nearly 50%. There were significant differences in the distributions of demographic characteristics between the groups (p < 0.05). After matching the demographic characteristics, differences in the prevalence of maternal mental health disorders between the groups reversed dramatically. Prevalence of moderate-to-severe depression, anxiety, and somatoform symptoms during the COVID-19 pandemic in this population (2.3, 9.6, and 20.8%, respectively) was significantly higher than those before the pandemic (0.3, 3.9, and 10%, respectively) (p < 0.05).ConclusionThe COVID-19 pandemic increased mental health risks among pregnant women. As a large proportion of pregnant women with mental health challenges delay their prenatal care or change healthcare facilities after the outbreak of public health emergencies, there is a need to establish a balanced healthcare system in medical institutions at all levels.